2013
DOI: 10.3109/08820538.2012.730101
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Operative Use of 5-Fluorouracil in Pterygium Surgery:  A Comparative Study

Abstract: This study suggests that antifibroproliferative therapy with intraoperative sponge 5-FLU is effective and safe. Its use may be a useful adjunct in primary pterygium surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…2 . There were 10 trials that compared bevacizumab to placebo [ 23 27 , 31 35 ], 14 trials that compared MMC to placebo [ 16 , 36 48 ], 2 that compared 5-FU to placebo [ 49 , 50 ], 2 that compared β-RT to placebo [ 51 , 52 ], 2 that compared MMC to 5-FU [ 53 , 54 ], 1 that compared MMC to β-RT [ 11 ], 1 that compared bevacizumab to MMC [ 55 ], and 1 that compared bevacizumab with 5-FU [ 56 ]. One study compared either bevacizumab or MMC to placebo [ 57 ] (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…2 . There were 10 trials that compared bevacizumab to placebo [ 23 27 , 31 35 ], 14 trials that compared MMC to placebo [ 16 , 36 48 ], 2 that compared 5-FU to placebo [ 49 , 50 ], 2 that compared β-RT to placebo [ 51 , 52 ], 2 that compared MMC to 5-FU [ 53 , 54 ], 1 that compared MMC to β-RT [ 11 ], 1 that compared bevacizumab to MMC [ 55 ], and 1 that compared bevacizumab with 5-FU [ 56 ]. One study compared either bevacizumab or MMC to placebo [ 57 ] (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…5-FUhas long been utilized in pterygium as an adjuvant to prevent recurrence. 18,19 However, use of 5FU as sole therapy to halt progression and recurrence of pterygium is relatively recent. Said et al reported that intralesional 5FU could halt pterygium progression; avoiding need for surgery.…”
Section: Discussionmentioning
confidence: 99%